Fatal infections in older patients with inflammatory bowel disease on anti-tumor necrosis factor therapy - Lee W.-S.; Azmi N.; Ng R.-T.; Ong S.-Y.; Ponnampalavanar S.S.L.; Mahadeva S.; Hilmi I. (Korean Association for the Study of Intestinal Diseases, 2024)
Indexed by SCOPUS